Civil-military relations in Latin America : new analytical perspectives - Pion-Berlin, David (University of North Carolina Press, 2001)
In nine essays, this volume offers theoretical insights into the dilemmas facing Latin American politicians as they struggle to gain full control over their military institutions. The contributors use a wide range of contemporary models to analyze political and economic reform.